PTH-086 Effect of Immunosuppressive Treatment on Interferon-Gamma Release Assays Prior to Biologic Treated Inflammatory Bowel Disease. (17th August 2016) - Bouri, S; Thi, AA; Wolfson, P; Owen, L; Abbara, A; John, L; Davidson, RN; Hart, AL
Abstract : Introduction: Indeterminate interferon-gamma release assay (IGRA) results when screening for latent tuberculosis infection (LTBI)prior to biologic use in inflammatory bowel disease (IBD) may delay biologic treatment initiation. Concomitant steroids affect IGRA result, however the impact of other immunosuppressive medications is less clear. We determine the effect of immunosuppressives on results of IGRAs. Methods: All patients treated with biologics from July 2013-November 2015 were identified from a pharmacy database. Electronic and clinical records were reviewed for IGRA result and concomitant immunosuppressive use. X2 was used to compare categorical data and univariate logistic regression using SPSS was used to determine likelihood of indeterminate tests with different immunomodulator medications (IMM). Results: 247 patients with IBD had an IGRA. Mean age: 36.9 years (range 8–85) and 54% were male. 78/247 (32%) had an indeterminate result and 35/78 (45%) patients had a repeat test; 17/35 (49%) had a second indeterminate result. 181/247 (73%) received at least one IMM prior to screening and 66 patients (27%) were not on any IMM (IMM-free). In the IMM group: 121/181 (67%) patients had thiopurines, 18/181 (10%) had corticosteroids, 25/181 (14%) had both, 9/181 (5%) had methotrexate and 7/181 (4%) had other IMMs at screening. 72/181 (40%) had a first indeterminate IGRA 59/181 (33%) had a second indeterminate result. In the IMM-free group: 6/66 (9.0%) had an indeterminate IGRA. Patients in IMM group were more likely to have an indeterminate results than patients in IMM-free group (33% v 9.0%, p = 0.00001). Each separate IMM group was more likely to be associated with an indeterminate IGRA result compared with those in IMM-free group: thiopurines (23%) p = 0.020, steroids (42%) p = 0.001, thiopurines and steroids (64%) p = 0.001, other (43%) p = 0.01 and methotrexate (44%) p = 0.008). The combination of steroids and thiopurines together was the strongest factor associated with an indeterminate result. High dose (Prednisolone >20 mg or intravenous Hydrocortisone) and low dose steroids (Prednisolone <20 mg or Budesonide) were equally likely to cause an indeterminate result (66.6% v 50.0%, p = 0.68). Conclusion: A combination of thiopurines and steroids gave the highest likelihood of an indeterminate IGRA result, although significant results occurred with all IMMs. This has implications for LTBI screening in IBD patients. Guidelines to address indeterminate IGRA results, perhaps with more focus on epidemiological risk may be helpful. There is an unmet need to have improved assessment tools for TB in patients on IMMs. Disclosure of Interest: None Declared